Ciberfeminismo: uma análise semiótica das estratégias de ativismos no Instagram - Pereira, Jessye Késsia de Carvalho (2023)
In contemporary times, amidst the speed of information and technological transformations, the boundaries between the physical and digital worlds gradually blur. In this context, electronic instruments play a significant role in transforming the roots of human language, profoundly modifying the mode of interaction. Consequently, they offer new possibilities for writing, reading, and social functioning, redefining the foundations of communication and paving the way for the emergence of new forms of expression and participation. This perspective includes social movements that enter the cyberspace realm, utilizing it as a tool to popularize and share their ideals. In this light, the present research aims to analyze, as a political and social discourse, the cyberfeminist strategies to gain followers presented by an Instagram page called "ferminismo." For this purpose, we draw on the theoretical framework of French Semiotic Discourse Studies by Greimas (1973, 1979), which characterizes the construction of meaning in a generative path, composed of levels: fundamental, narrative, especially the spheres of veridiction and passions, and discursive. Additionally, we rely on the postulates of Floch (1985, 1995) regarding verbovisual texts, developed in Brazil by Teixeira (2009, 2008). Furthermore, the research is enriched by theorists discussing the formation of the feminist movement and the issue of activism in the digital era, notably Perrot (1998), Duarte (2019), Dutra (2019), Castells (2013), and other scholars contributing to the construction of the history of feminist discourses, ranging from the 18th and 19th centuries to the present day. Our analysis corpus consists of four posts, and the results demonstrate that the most prevalent strategies are: informing or raising awareness, empowering, and using irony.